Analisis Yuridis Dugaan Tindak Pidana Korupsi dalam Pengelolaan Aset Daerah pada Kasus Mega Mall Bengkulu - Hanif Asyauqi; Ilham Pratama; Muhammad Ghifari Satria Negara; Aufa Kamula; Ade Saputra98 (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Corruption remains one of the most serious legal problems in Indonesia, particularly in the management of public resources and regional assets. One of the cases that attracted public attention is the alleged corruption related to the management of regional assets connected to Mega Mall Bengkulu. This study aims to analyze the juridical aspects of alleged corruption crimes in the management of regional assets in the Mega Mall Bengkulu case. The research method used is normative juridical research with a statutory approach, conceptual approach, and case approach. The results show that irregularities in agreements, misuse of authority, and lack of transparency in asset management may potentially lead to state financial losses. Such actions can fulfill the elements of corruption crimes as regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. Therefore, strengthening supervision and transparency in regional asset management is necessary to prevent corruption practices in local government administration.